Professional trajectories of ex-normalistas of the Rui Barbosa education institute: the construction of the teaching exercise (Aracaju-SE, 1920-1950) - Freitas, Anamaria Gonçalves Bueno de (Cadernos CERU, 2000)
This study intends to analyze the professional performance of women who attendend the Rui Barbosa Institute of Education in Aracaju, Sergipe in the 1920s and 1930s. An analysis of official documents and women life-histories reveals their professional accomplishments in the field of education, thereby challenging the stereotype of female students who attended school only in search of a husband.